The Fake news society? an interactive storytelling website on how historical revisionism affects a millennial's narrative in creating false impressions regarding the history of martial law - Valencia, Camille B.
The history of Martial law has been widely debated by generations of the past as well as the present, regarding the truth of what really happened during Marcos' term. Since today's generation never lived through or experienced Martial Law firsthand, they are left with no choice but to rely heavily on books, accounts of their families and relatives who have been through it, and of course the fastest and most convenient way of gaining knowledge today known as the internet. With the help of the internet, information is always within reach of today's generation. It also enables everyone especially millennials to participate in several social media sites that allows access and share contents to and from people around the world. The millennial generation, born between 1981-1996 according to the U.S. think tank Pew Research Center, just five years after Marcos was ousted, make up one-third of the population of the Philippines and are the generation who grew up more dependent on technology.